Species diversity, hotspot congruence, and conservation of North American damselflies (Odonata: Zygoptera) - Zhao, Zhengxue; Feng, Xueli; Zhang, Yubo; Wang, Yingjian; Zhou, Zhengxiang (Frontiers in Ecology and Evolution, 2023)
The rapid extinction of species is of considerable concern for biodiversity conservation. Identifying the drivers of species and hotspot diversity is beneficial for developing conservation strategies. Studies on insects have mainly focused on terrestrial species and rarely on aquatic species. Using 135,208 georeferenced occurrence records of 296 damselflies across North America, their species richness and endemism (represented by weighted endemism) patterns were mapped in a 100 × 100-km grid size, and the effects of environmental variables on species richness and endemism were investigated using generalized linear models and hierarchical partitioning. Subsequently, the top 5% grids with species richness and weighted endemism were separately selected as hotspots, and their congruence was evaluated. Finally, species diversity hotspots were identified by integrating two types of hotspot grids, and gap analysis was performed to evaluate their conservation status. The variables of temperature and water availability had the strongest influence on species richness and endemism, respectively. Low congruence among species richness and endemism hotspots was observed. Moreover, four species diversity hotspots were identified: region of the eastern United States and southeastern Canada, southwestern United States, central Mexico, and southernmost North America. Approximately 69.31% of hotspot grids are not covered by the existing protected areas, presenting a significant conservation gap. The habitats of taxonomic groups should be considered when identifying the most common driving mechanisms of endemism. Strengthening the establishment of protected areas in regions with conservation gaps is urgently needed to promote the conservation of damselflies in North America.